The Use of Think-Aloud and Instant Data Analysis in Evaluation Research: Exemplar and Lessons Learned - Joe, Jonathan (J Biomed Inform, 2015)
While health information technologies have become increasingly popular, many have not been formally tested to ascertain their usability. Traditional rigorous methods take significant amounts of time and manpower to evaluate the usability of a system. In this paper, we evaluate the use of instant data analysis (IDA) as developed by Kjeldskov et al. to perform usability testing on a tool designed for older adults and caregivers. The IDA method is attractive because it takes significantly less time and manpower than the traditional usability testing methods. In this paper we demonstrate how IDA was used to evaluate usability of a multifunctional wellness tool, discuss study results and lessons learned while using this method. We also present findings from an extension of the method which allows the grouping of similar usability problems in an efficient manner. We found that the IDA method is a quick, relatively easy approach to identifying and ranking usability issues among health information technologies.